1997
DOI: 10.1111/j.2044-8341.1997.tb01912.x
|View full text |Cite
|
Sign up to set email alerts
|

The correlates of antenatal attachment in pregnant women

Abstract: Maternal-foetal attachment represents the earliest and most basic form of human intimacy, and has both theoretical and clinical significance. Utilizing a previously published self-report questionnaire to assess antenatal attachment, the present paper explores its correlates using 238 women in the third trimester of pregnancy. Extrapolating from studies of maternal-infant attachment, it was hypothesized that depression and a lack of social support would be detrimental to the development of maternal antenatal at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
219
4
28

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(274 citation statements)
references
References 0 publications
21
219
4
28
Order By: Relevance
“…However, there appears to be a lack of empirical and reliable studies that support this view (Mercer et al, 1988) as several researchers have found no significant differences in foetal attachment scores between women with high-risk and normal pregnancies (Hsu & Chen, 2001;Kemp & Page, 1987). There is also a lack of consistency in the findings of studies examining the psychosocial correlates of maternal-foetal attachment in high-risk populations, with some authors reporting no relationships between psychological variables such as anxiety and depression, and maternal-foetal attachment (Mercer et al, 1988), and others (Condon & Corkindale, 1997) finding that these variables (depression, anxiety and other Profile of Mood Scale scores) strongly impact upon the quality of attachment experience. This inconsistency is highlighted by Laxton-Kane and Slade's (2002) review of the literature, where they conclude that apart from the research pertaining to conception via in-vitro fertilisation, no conclusions about the effect of risk on prenatal attachment can be made due to the limited number of studies published.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…However, there appears to be a lack of empirical and reliable studies that support this view (Mercer et al, 1988) as several researchers have found no significant differences in foetal attachment scores between women with high-risk and normal pregnancies (Hsu & Chen, 2001;Kemp & Page, 1987). There is also a lack of consistency in the findings of studies examining the psychosocial correlates of maternal-foetal attachment in high-risk populations, with some authors reporting no relationships between psychological variables such as anxiety and depression, and maternal-foetal attachment (Mercer et al, 1988), and others (Condon & Corkindale, 1997) finding that these variables (depression, anxiety and other Profile of Mood Scale scores) strongly impact upon the quality of attachment experience. This inconsistency is highlighted by Laxton-Kane and Slade's (2002) review of the literature, where they conclude that apart from the research pertaining to conception via in-vitro fertilisation, no conclusions about the effect of risk on prenatal attachment can be made due to the limited number of studies published.…”
Section: Introductionmentioning
confidence: 69%
“…Social support was investigated but was eliminated from the analysis at an early stage, as it was not related to either subscale of attachment. Existing literature pertaining to social support is contradictory: Mercer et al (1988) found no relationship between received social support and attachment for high-risk pregnant women and their partners; while Condon and Corkindale (1997) concluded that a lack of social support was detrimental to the development of maternal antenatal attachment in normal pregnancies. The current results do little to clarify the situation, possibly due (at least in part) to the low variability in satisfaction with social support (mean55.49, SD51.09) in this study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Müller defined prenatal attachment as the unique, affectionate relationship that develops between the pregnant woman and the fetus (Müller, 1993). According to Condon & Corkindale, 1997, the concept prenatal attachment include the following five factors; wishing for knowledge about the unborn baby, happiness for the interplay with the baby, wishing for protecting the baby and satisfying its needs, worrying about losing the baby or that something will be wrong with the baby, and that the baby's needs have priority over the own needs. They developed the instrument MAAS (maternal antenatal attachment scale).…”
Section: Maternal-fetal Attachmentmentioning
confidence: 99%
“…태아애착이 높은 임부들은 출산 후 영아와 더 많은 상호작용을 하는 것으로 나타나고 있으며 (White et al, 1999;Davoudi, 2014), 이러한 모아 상호작용은 영유아기 발달에 중요한 역할을 한다. 그 예로, 모아 상호작용은 유아 가 주변 환경을 더 적극적으로 탐구하도록 만들고, 당면한 문제를 해결하도록 하며, 사회적 발달에도 큰 영향을 미친다 (Condon et al, 1997;Siddiqui et al, 2000;Kim JS et al, 2002;Alhusen et al, 2013).…”
unclassified